Reticular synthesis, topological studies and physicochemical properties of a 3D manganese(II) coordination network [Mn3(BTC)2(DMSO)4]n - Flores, Leonã da Silva; Rosa, Roselia Ives; Martins, Jefferson da Silva; Pinho, Roberto Rosas; Diniz, Renata; Corrêa, Charlane Cimini (European Journal of Chemistry, 2019)
In order to build a metal-organic framework with mixed ligands (acid-acid), a 3D coordination network based on manganese metal center was obtained [Mn3(BTC)2(DMSO)4]n; where BTC = Benzene-1,3,5-tricarboxylic acid and DMSO = Dimethylsulfoxide. The crystal structure was determined by single crystal X-ray diffraction, showing the assembly of a tridimensional 3,6-connected non-entangled polymeric network, with RTL topology. The secondary building unit (SBU) acts as a node of the 3-periodic expansion and involves carboxylate- and oxo-bridged metals. The DMSO employed in the synthesis is chemically involved in the coordination as a µ2-O bridge between distinct manganese metal centers. The structural characterization of the material was supported by spectroscopic (infrared absorption and Raman scattering), thermal (TG, DTG, and DTA) and elemental analysis.